Evaluation of the effect of PBL on the change of self-direction competition in university students in distance education. - Aux Moreno, Lorena Jaqueline (SATHIRI, 2019)
Competency- based education allows students to develop skills and abilities that respond to the needs of communities that contribute to improving their job performance.The objective of the research was to develop the competence of self-direction through the implementation of the didactic approach called problem-based learning.For the development of the research, a mixed method with a quasi- experimental and transactional design was used over a period of 30 days applied from August 30th to September 30th2017, at the Corporación Universitaria Minuto de Dios – Centro Regional Pasto, Higher Education Institution with a distance learning methodology, a convenience sample of 20 first semester students was selected, two groups were created, an experimental group to which the strategy of the PBL is applied and a control group that continues with the traditional learning approach. The instruments employed were the questionnaire of the self-irecting section of the Individual Generic Competencies Questionnaire of Olivares and López, (2015) and the observation in the classroom, which allowed to measure the changes in the dimensions of learning strategy, emotion management and ongoing improvement. The findings pointed out that there are positive changes in the dimensions studied that lead to the development of self-directed competence, in the students to whom the ABP strategy was applied, who learned to work in a team, analyze the contexts with critical, reflective and proactive thinking.